EDUKASI INTERAKTIF PENCEGAHAN BULLYING PADA SISWA SEKOLAH DASAR DAN TAMAN KANAK-KANAK DI NAGARI KOTO GADANG - Siti Naila Safira; Intan Cahyani; Adheliana; Zahwa Azzura; Deo Tri Andika; Miftahul Khair (STKIP Subang, 2026)
Bullying remains a common problem in elementary education and can negatively impact children's psychological, emotional, and social development. Therefore, preventive measures are needed through educational activities that can improve students' understanding of bullying behavior from an early age. This community service activity aims to increase students' understanding and awareness of the meaning, forms, and impacts of bullying through an interactive educational approach. The activity was carried out in Nagari Koto Gadang Anam Koto, involving students from SDN 12 Koto Gadang, SDN 33 Koto Gadang, and TK Harapan Koto Gadang. The method used was interactive education, which included delivering material through visual media, illustrated stories, role-playing simulations, and twoway discussions tailored to the developmental stage of the students. The results of the activity showed an increase in students' understanding in identifying various forms of bullying, understanding the emotional impact experienced by victims, and the emergence of empathy and a commitment to refrain from bullying behavior. Thus, socialization through an interactive educational approach can be an effective preventive strategy in supporting the creation of a safe, inclusive, and conducive learning environment from an early age.